The impact of pool sharing on the distribution of playing talent in the n-team leagues - Fujimoto, M. (Journal of Sports Economics, 2025)
This article exactly determines the impact of pool sharing on the talent distribution in the league for a general n-team model where each team is a profit maximizer, each team has the Nash conjectures, each team's revenue depends only on relative team qualities, and the supply of talent is fixed. It is shown that when a pool-sharing agreement is introduced, larger-market teams with greater marginal revenues of winning before sharing will demand more wins and talents than before sharing, while smaller-market teams with smaller marginal revenues of winning before sharing will demand less wins and talents than before sharing.